ANALISIS SEMIOTIKA FOTOGRAFI â€œALKISAHâ€ KARYA RIO MOTRET (RIO WIBOWO) - Huda, Muhamad Miftahul; Hamim, Hamim; Wibowo, Judhi Hari (Universitas 17 Agustus 1945 Surabaya, 2018)
This research is motivated by the development of photography as a medium of visualcommunication to create an image as well as provide and deliver a message. One photographerIndonesia, Rio photographed create photographic works of folklore Indonesian theme with the title